Biomechanical Analysis of Movement in Basic Squat Exercise: Impact on Efficiency and Injury Risk - Lisna Wijayanti; Nelly Anggraini; Deden Akbar Izzudin; Qorry Armen Gemael (UNIVERSITAS NEGERI MAKASSAR, 2024)
The basic squat exercise is a strength exercise that is widely used to strengthen the muscles of the lower body, including the quadriceps, hamstrings and glutes. However, improper technique in performing squats can increase the risk of injury. This article aims to analyze the biomechanics of movements in squat training, with a focus on how correct technique can influence exercise efficiency and injury risk. This study used one subject as a sample to evaluate body posture and joint movement angles during exercise. The measuring instrument used is a goniometer to measure the angles of the knee and hip joints in various squat positions. Research results show that correct squat technique, with appropriate joint angles, not only increases exercise efficiency but also reduces the risk of injury. Conversely, incorrect technique can cause excessive stress on the knee and hip joints. These findings emphasize the importance of correct technique training in squat exercises to achieve maximum benefits and reduce the potential for injury.